Low ferroptosis score predicts chemotherapy responsiveness and immune‐activation in colorectal cancer - Yang Lv; Qing‐Yang Feng; Zhi‐Yuan Zhang; Peng Zheng; De‐xiang Zhu; Qi Lin; Si‐min Chen; Yi‐Hao Mao; Yu‐Qiu Xu; Mei‐ling Ji; Jian‐Min Xu; Guo‐dong He (Cancer Medicine, 2023)
Abstract Background Existing studies for ferroptosis and prognosis in colorectal cancer (CRC) were limited. In this study, we aim to investigate the prognostic role of ferroptosis markers in patients with CRC and exploration of its micro‐environmental distributions. Methods Immunohistochemical staining was performed for CRC patients’ tissue microarray. Selection and prognostic validation of markers were based on mRNA data from the cancer genome atlas (TCGA) database. Gene Set Enrichment Analysis (GSEA) was performed to indicate relative immune landmarks and hallmarks. Ferroptosis and immune contexture were examined by CIBERSORT. Survival outcomes were analyzed by Kaplan‐Meier analysis and cox analysis. Results A panel of 42 genes was selected. Through mRNA expression difference and prognosis analysis, GPX4, NOX1 and ACSL4 were selected as candidate markers. By IHC, increased GPX4, decreased NOX1 and decreased FACL4 indicate poor prognosis and worse clinical characteristics. Ferroptosis score based on GPX4, NOX1 and ACSL4 was constructed and validated with high C‐index. Low ferroptosis score can also demonstrate the better progression free survival and better adjuvant chemotherapy (ACT) responsiveness. Moreover, tumor with low ferroptosis score tend to be infiltrated with more CD4+ T cells, CD8+ T cells and less M1 macrophage. Finally, we found that IFN‐γ was potentially the central molecule at the crossroad between ferroptosis and onco‐immune response. Conclusion Ferroptosis plays important role on CRC tumor progression, ACT response and prognosis. Ferroptosis contributes to immune‐supportive responses and IFN‐γ was the central molecule for this process.